Improved counterplan for interference in same-band information transmission and reception - Rhee, Eugene; Cho, Junhee (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Wireless communication technologies operating in the 2.4 GHz band, such as Wi-Fi, Bluetooth, ZigBee, and others, often face challenges related to mutual interference. These technologies share the same unlicensed frequency spectrum, which can lead to various types of interference, affecting performance, reliability, and data throughput. This paper addresses the issue of mutual interference in communications occurring within frequency bands commonly used in daily life. Through this, it conducts an in-depth study on information processing between wireless devices and the control of communication components. Specifically, it examines interference phenomena in the widely used 2.4 GHz band by analyzing communication methods where such interference is likely to occur. By investigating the characteristics of Wi-Fi, Bluetooth, and ZigBee, this study analyzes interference phenomena and proposes an algorithm to mitigate them. To mitigate this, this paper proposes a multi-layered method integrating adaptive filtering, dynamic frequency allocation, advanced error correction, and intelligent scheduling mechanisms.